The shift-of-strategy (SoS) approach: using evidence strategically to influence suspects’ counter-interrogation strategies - Luke, Timothy J. (Psychology, crime & law, 2023)
The Shift-of-Strategy (SoS) approach is an extension of the Strategic Use of Evidence technique. In the SoS approach, interviewers influence suspects’ strategies to encourage suspects to become more forthcoming with information by challenging discrepancies between their statements and the available evidence, in a non-accusatory manner. Our aim was to test the effectiveness of two variations of the SoS approach, one in which the interviewer responded immediately to any discrepancies with the evidence (Reactive) and one in which the interviewer only responded to severe discrepancies (Selective). We predicted that the SoS approach conditions would be more effective at eliciting new information from mock suspects, compared to direct questioning. In a laboratory experiment, N = 300 mock suspects committed a simulated crime and were interviewed using one of the two versions of the SoS approach or with an interviewing approach that did not involve the presentation of evidence. The Reactive version of the SoS approach was more effective than direct questioning at eliciting new information from mock suspects. The Reactive technique also led participants to change their strategies during the interview. The present experiment provided initial support for the core principles of the SoS approach.